1928
DOI: 10.1136/bmj.2.3542.935
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Plasma Cholesterol and Basal Metabolism

Abstract: PREVENTION OF COMPLETB EUPTURU OF THH PEINEUM. 1J 835 lefore the tear extends into the rectum is largely a matter of luck, unless the obstetrician can take active steps to limit the (damnage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

1930
1930
1964
1964

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Contrary to the findings in Graves' disease [Gardner and Gainsborough, 1928], the production of an experimental hyperthyroidism did not result in any decrease in the blood cholesterol content, in fact the average of six estimations was slightly higher than the corresponding controls.…”
Section: Methodscontrasting
confidence: 99%
“…Contrary to the findings in Graves' disease [Gardner and Gainsborough, 1928], the production of an experimental hyperthyroidism did not result in any decrease in the blood cholesterol content, in fact the average of six estimations was slightly higher than the corresponding controls.…”
Section: Methodscontrasting
confidence: 99%
“…Some of these patients, notably A44014, 6, 5253 and P1667, required large doses to effect these results. In Tables III and IV (with the excep-tion of P1667 who was injected intravenously with large doses of thyroxin) the decreases in cholesterol in 8 of the 12 patients were between 11 and 65 mgm.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, patients with low basals and low lipoids often are asthenic in physique (33) and are troubled by tension, irritability, tremulousness and insomnia. The administration of thyroid to such persons seems contraindicated, as for example in (6) Table III. This man had found work difficult because of weakness and easy fatigability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of workers have reported that in patients with hyperthyroidism the blood or serum cholesterol may be within normal limits (1,3,15,28,30,44,52), or sometimes high (17,22,29,39,40,51). That there is no clear-cut relation between basal metabolic rate and cholesterol is probably due to many factors.…”
mentioning
confidence: 99%